FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT MODERASI BERAGAMA DI KALANGAN PEMUDA KRISTEN - Sara Kombong; Delpina Riu, Yuliani Rangan, Arsiati Toding Tiku, Yerfa Siling (Jurnal Salome : Multidisipliner Keilmuan, 2023)
Religious moderation has become a crucial issue in understanding how the younger generation in Christian communities navigate their religious beliefs in the context of a continuously evolving society. Therefore, this research aims to investigate the factors influencing the level of religious moderation among young Christians. This literature review involves analyzing literature from various sources that discuss key aspects that can influence attitudes toward religious moderation. Through the method of literature review or literary study, this research identifies several key factors that can play a pivotal role in shaping the level of religious moderation among young Christians. These factors include demographic aspects such as age and education, the influence of social environments including family and peers, the role of the church and participation in social service activities, the impact of media and technology, as well as challenges related to religious identity that young Christians may face. The importance of religious education and experiences in the church is also a focal point in this study, considering how understanding religion and participation in religious activities can shape attitudes toward religious moderation. Furthermore, the impact of religious identity crises and spiritual questions is also a relevant aspect in evaluating these factors. The findings of this research are expected to provide a solid foundation for further studies on the factors influencing religious moderation among young Christians. These findings are anticipated to make a significant contribution to spiritual guidance, the development of religious education programs, and the formulation of more effective church policies to support the younger generation of Christians in managing their religious beliefs moderately amid the challenges of the times.